Heurísticas aplicadas à comunicação visual de informação científica: uma pesquisa exploratória - Barbosa, Zanalis Alves (2021)
The result of scientific research needs to be communicated and, at the same time, communicative. In recent years, Digitization has affected the Visual Communication of Scientific Information. This exploratory study was carried out in two main stages. In the first stage, bibliographical research characterized the main elements of Visual Communication, the effects of Digitization and communication through Graphics. The second stage of the study brought together several guidelines and proposals on the process of building good visual communication. From these stages, it was possible to propose the CVGC Heuristic Model, a heuristic based on questions to assist the process of visual communication of scientific information through graphics.